Predictors of maternal dietary quality and dietary inflammation during pregnancy: An individual participant data meta-analysis of seven European cohorts from the ALPHABET consortium. Issue 9 (September 2022) - Aubert, Adrien M.; Chen, Ling-Wei; Shivappa, Nitin; Cooper, Cyrus; Crozier, Sarah R.; Duijts, Liesbeth; Forhan, Anne; Hanke, Wojciech; Harvey, Nicholas C.; Jankowska, Agnieszka; Kelleher, Cecily C.; de Lauzon-Guillain, Blandine; et al.
Summary: Background & aims: Maternal diet during pregnancy is a modifiable behaviour which plays an important role in maternal, neonatal and child health outcomes. Thus, knowledge of predictors of dietary quality and dietary inflammatory potential in European countries may contribute to developing maternal diet-related public health policies that target specific at-risk populations in Europe. Methods: We used harmonised data from >26, 000 pregnant women enrolled in the ALSPAC, EDEN, Generation R, Lifeways, REPRO_PL, ROLO and SWS cohorts, as part of the ALPHABET consortium. Maternal dietary quality and inflammatory potential were assessed using the Dietary Approaches to Stop Hypertension (DASH) and the energy-adjusted Dietary Inflammatory Index (E-DII). We conducted an individual participant data meta-analysis to investigate the maternal sociodemographic, health and behavioural predictors of maternal diet before and during pregnancy. Results: DASH and E-DII scores were moderately correlated: from −0.63 (95% CI: −0.66,  −0.59) to −0.48 (95% CI: −0.49,  −0.47) across cohorts. Higher maternal age, education, household income, and physical activity during pregnancy were associated with a better dietary quality and a more anti-inflammatory diet. Conversely, multiparity and smoking during pregnancy were associated with a poorer dietary quality and a more proinflammatory diet. Women with obesity had a poorer pregnancy dietary quality than women with a normal body mass index range. Conclusions: The results will help identify population subgroups who may benefit from targeted public health strategies and interventions aimed at improving women's dietary quality during pregnancy.